Orphan devices: yesterday is history; tomorrow is mystery: towards a European orphan device directive?. Issue 1 (December 2016) - Dooms, Marc
Abstract Background Regulatory and economic frameworks stimulated the research and development of orphan drugs, but very little has been done for devices necessary for the in-vivo diagnosis, prevention and treatment of life-threatening conditions with a low prevalence/incidence. Discussion A general public consultation in Europe has shown a positive attitude towards an "orphan device" directive. The United States of America have a Humanitarian Use Device exemption, but Europe is still waiting for such a stimulating framework. Post-marketing surveillance ("materio-vigilance") will be necessary for follow-up, patient-reported outcome measures (quality of life versus survival) needed and off-label use data available for patient-safety reasons. Summary The marketing period for devices is shorter than for medicinal products. Incentives are necessary to stimulate research and development of such "orphan devices" especially when surgical intervention is the only option.